Pengaruh Model Pembelajaran Picture and Picture Terhadap Keterampilan Menulis Bahasa Indonesia Siswa Kelas II SDN 19 Tanjung Harapan - Monalisa Sinaga; Liliana Agusfrina Nasution; Hernita hernita; Wisman Hadi; Elly Prihasti Wuriyani (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This study aims to explain the effect of picture and picture learning model on writing skills of grade II students of SDN 19 Tanjung Harapan. This study uses a type of pseudo-experiment with a non-equivalent control group design. The population in this study was all grade II students of SDN 19 Tanjung Harapan with sample selection using random sampling. The results of the study explained from the description test instrument totaling 1 valid test item. The data was analyzed using the polled variant t-test. The mean writing skill of the experimental group = 0.40, the mean writing skill of the control group = 0.25. This result explained that there was a good difference between the experimental group that used the picture and picture learning model and the control group that used the lecture model. The proof is with tcount = 6.523 at 5% significance level with dk = (36+34)-2 = 68 obtained ttable = 2.500. Thus, the conclusion is that the picture and picture learning model has a significant effect on the writing skills of grade II students of SDN 19 Tanjung Harapan.